Analysis of Students' Difficulties in Learning English Skills at Boarding Islamic Schools - Sofyan, Sofyan; Widyantoro, Agus; Adoma, Prince Owusu (International Journal of Contemporary Studies in Education, 2023)
Learning English as a second language poses challenges for students worldwide, and this holds true for students studying at boarding Islamic schools as well. This research aims to analyze the difficulties faced by students in acquiring English language skills within the unique context of boarding Islamic schools. By identifying the specific challenges encountered by these students, educators and policymakers can develop targeted strategies to enhance English language learning in this educational setting. The study utilizes a qualitative research approach, involving interviews, observations, and document analysis to gather data from students and teachers. The findings highlight common difficulties faced by students in learning English skills, including linguistic barriers, limited exposure to English outside the school environment, curriculum constraints, and lack of resources. The research concludes with recommendations for addressing these challenges and improving English language learning outcomes in boarding Islamic schools.